2021
DOI: 10.1021/acsami.1c07257
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Filtration Membranes Based on PVDF-co-HFP Nanofibers with the Addition of Medium-Chain 1-Monoacylglycerols

Abstract: The efficiency of filtration membranes is substantially lowered by bacterial attachments and potential fouling processes, which reduce their durability and lifecycle. The antibacterial and antifouling properties exhibited by the added materials play a substantial role in their application. We tested a material poly(vinylidene fluoride)-co-hexafluoropropylene (PDVFco-HFP) based on an electrospun copolymer, where an agent was incorporated with a small amount of ester of glycerol consecutively with caprylic, capr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…This is due to the character of MAG and the type of its adsorption with hydrophilic groups oriented into the surrounding. In the previous studies, a similar behavior at PVB/MAG 10 and PVDF/MAG 12 fibrous membranes was found [ 74 , 75 ].…”
Section: Resultssupporting
confidence: 80%
“…This is due to the character of MAG and the type of its adsorption with hydrophilic groups oriented into the surrounding. In the previous studies, a similar behavior at PVB/MAG 10 and PVDF/MAG 12 fibrous membranes was found [ 74 , 75 ].…”
Section: Resultssupporting
confidence: 80%
“…The peaks at 1729, 2849, and 2957 cm −1 can be observed in the zein film enriched with active agents ( Figure 3 b,c), revealing the C=O and C-O stretching pertaining to the structure of the monolaurin molecule. A predominant role of monolaurin was confirmed, since the spectra of the sample with monolaurin and thyme essential oil did not reveal any significant changes [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PAN-NF allows bacterial growth after 2 hours of incubation, which translates to just a 9.6 % reduction rate compared to that of the control (commercial cotton fabric). On the other hand, VIO-NF exhibited effective biocidal characteristics with a reduced rate of 75.5 % within just 2 hours, indicating that VIO-NF is quite effective even when benchmarked against previously reported composite polymer nanofibers ( Table S2 ) [18] , [19] , [20] , [21] . In particular, the porous nanofiber network of VIO-NF enlarges the contact area for the target bacteria to induce a biostatic effect, immobilizing the bacteria and accelerating cell death.…”
Section: Resultsmentioning
confidence: 70%
“…One approach to mitigate the issues with pathogen contamination is to directly apply antiviral and/or antimicrobial agents ( e.g. , polyanionic/cationic polymers, metal-organic frameworks, graphene oxides, and metal particles) onto the filter matrix, either on the outer surface and/or in the interior matrix, to inactivate the captured viruses as well as bacterias [5] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . However, previous studies often accompanied several problems such as poor adhesion, nonuniform coverage, and heavyweight of antimicrobial agents, making them impractical [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%